CHILDHOODS AND THE INFRAORDINARY:: NOTES TO RESIST CONTEMPORARY ACCELERATION - Neiss, Alessandra; Habowski, Adilson Cristiano (Literatura em Debate, 2025)
Contemporary society is characterized by a fast pace, in which the appreciation of large and fast productions prevails. In this context, other aspects of life, such as experiences, end up relegated to the background. Inserted in this scenario are childhoods, which suffer the effects of these accelerations. At home, in schools or in any other social space, childhoods have been progressively removed from the possibility of observing, imagining and creating, since adult-centric demands impose different priorities. In this essay, we investigate childhood times and the centrality of experiences through a bibliographic study with a qualitative approach. Initially, we base our discussion on contemporary acceleration on the reflections of Hartmut Rosa. We then promoted a dialogue with authors such as Walter Omar Kohan, Walter Benjamin and Giorgio Agamben, analyzing the need to give new meaning to the times and spaces of childhood. Finally, we explore the concept of infraordinary, developed by Georges Perec, which highlights the importance of human experiences anchored in the subtleties and particularities of everyday life – often neglected in a fast-paced society, but fundamental for a deeper and more sensitive understanding of life. From these perspectives, we conclude that it is essential to question and break with traditional hegemonic models. It is necessary to open fissures that allow childhoods to be crossed by significant experiences, recognizing and celebrating the beauty present in the infraordinary as an essential dimension of existence.